2020
DOI: 10.1038/s41565-019-0600-1
|View full text |Cite|
|
Sign up to set email alerts
|

Vitamin lipid nanoparticles enable adoptive macrophage transfer for the treatment of multidrug-resistant bacterial sepsis

Abstract: Sepsis, a condition caused by severe infections, affects more than 30 million people worldwide every year and remains the leading cause of death in hospitals 1,2 . Moreover, antimicrobial resistance has become an additional challenge in the treatment of sepsis 3 , and thus, alternative therapeutic approaches are urgently needed 2,3 . Here, we show that adoptive transfer of macrophages containing antimicrobial peptides linked to cathepsin B in the lysosomes (MACs) can be applied for the treatment of multi-drug … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
193
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 188 publications
(204 citation statements)
references
References 27 publications
0
193
0
3
Order By: Relevance
“…In particular, macrophages and neutrophils, phagocytic cells acting as the first line of defence against infection, engulf bacteria within minutes of infection [56]. The engulfed bacteria are then destroyed by fusion with acidic lysosomes, which deliver digestive enzymes, bactericidal proteins (e.g., lysozyme), proton pumps, ROS and reactive nitrogen species to the phagosome [57,58].…”
Section: Targeting Intracellular Bacteriamentioning
confidence: 99%
See 3 more Smart Citations
“…In particular, macrophages and neutrophils, phagocytic cells acting as the first line of defence against infection, engulf bacteria within minutes of infection [56]. The engulfed bacteria are then destroyed by fusion with acidic lysosomes, which deliver digestive enzymes, bactericidal proteins (e.g., lysozyme), proton pumps, ROS and reactive nitrogen species to the phagosome [57,58].…”
Section: Targeting Intracellular Bacteriamentioning
confidence: 99%
“…Although phagolysosomal killing is usually quite effective, a number of bacteria, including Escherichia coli and S. aureus, have developed methods to survive this process, allowing them to reside within the cell for prolonged periods of time [56,58]. These pathogen-containing immune cells can then disseminate the bacteria throughout the body, where they can infect other tissues, thereby causing chronic or recurrent infections [56,59].…”
Section: Targeting Intracellular Bacteriamentioning
confidence: 99%
See 2 more Smart Citations
“…[160] More recently, it was reported that vitamin C lipid NP, used to deliver antimicrobial peptide to macro phage lysosomes, show remarkable antimicrobial activities in fighting multidrug-resistant bacteria, including S. aureus and E. coli, even in immunocompromised septic mice. [161] It should be noted that the vast majority of the results showing little toxic or immunomodulatory effects of NM was obtained in healthy animals or under standard cell culture conditions. The possibility that NM may impact the innate immune defensive mechanisms of weaker, immunocompromised organisms, or under chronic inflammatory conditions is, therefore, still possible and remains under-investigated.…”
Section: Nanomaterials and Global Defense To Infection/damagementioning
confidence: 99%